The Wood Wide Web as a blueprint for carbon-neutral cities: a biomimetic model for adaptive energy sharing - Rahubadda, Rahubadda Vithanage Ashen Dilruksha; Manewa, Anupa; Anagal, Vaishali; Siriwardena, Mohan (Frontiers in Built Environment, 2025)
As urbanization accelerates and climate targets become increasingly urgent, conventional centralized energy systems are proving insufficient to support the transition toward low-carbon, resilient cities. This study proposes a novel biomimetic framework for urban energy systems, inspired by the Wood Wide Web, the mycorrhizal networks in forest ecologies that enable mutualistic, decentralized resource exchange. Guided by the biomimicry spiral methodology, the ecological principles of cooperation, adaptability, and distributed resilience are abstracted into a three-layer urban energy model comprising on-site renewable generation, peer-to-peer (P2P) energy sharing, and grid integration for redundancy. The model was operationalized through Building Information Modeling (BIM) simulations comparing two urban building clusters: a conventional baseline and a biomimetic cluster anchored by a high-performance “mother tree” structure, modeled after London’s Gherkin. Autodesk Revit’s Energy Analysis, Solar Radiation Analysis, and Carbon Insights tools were used to evaluate each scenario’s energy performance, solar generation potential, and carbon emissions. Results reveal a transformative impact: cooperative energy redistribution enabled multiple buildings to reach net-zero emissions, while the mother tree intervention alone achieved a 46% reduction in annual cluster-wide carbon output. The results demonstrate how decentralized, cooperative energy systems, modeled on ecological intelligence, can enhance system-wide resilience and carbon neutrality. This research advances biomimicry from conceptual metaphor to actionable infrastructure design, offering a scalable blueprint for regenerative, climate-adaptive urban energy systems. By embedding ecological principles into the built environment, cities can evolve into cooperative, circular systems aligned with nature’s logic and sustainability goals.